Target Identification and Validation in Drug Discovery Methods and Protocols - Moll, Jurgen; Colombo, Riccardo; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
The major reason for the elevated costs of drug development in the pharmaceutical industry is the high attrition rate. In Target Identification and Validation in Drug Discovery: Methods and Protocols, expert researchers in the field detail many of the methods which are now commonly used to identify and validate new target. These include methods and approaches covering biochemical, cell based, in vivo models and translational methods. Chapters also include selected case reports that demonstrate the integration of these technologies to real life experiences and to demonstrate the multiple use of more than one technology to increase knowledge on a specific target. These Written in the highly successful Methods in Molecular Biology™ series format, the chapters include the kind of detailed description and implementation advice that is crucial for getting optimal results in the laboratory.   Thorough and intuitive, Target Identification and Validation in Drug Discovery: Methods and Protocols contains a comprehensive list of essential methods and clear protocols to follow.
The Path to Oncology Drug Target Validation – an Industry Perspective -- Identification of Aptamers as Specific Binders and Modulators of Cell-Surface Receptor Activity -- The Design and Structure-functional Properties  of DNA-based Immunomodulatory Sequences -- siRNA Design Principles and Off-target Effects -- Western Blot Evaluation of siRNA Delivery by pH Responsive Peptides -- High Throughput RNAi Screening for the Identification of Novel Targets -- Integration of RNAi and Small Molecule Screens to Identify Targets for Drug Development -- CellProfiler and KNIME: Open Source Tools for High Content Screening -- PARP Inhibition as a Prototype for Synthetic Lethal Screens -- Structure-Based Target Druggability Assessment -- Validating Pharmacological Disruption of Protein-protein Interactions by Acceptor Photobleaching FRET Imaging -- Systematic Analysis of Complex Signal Transduction Pathways using Protein Fragment Complementation Assays -- Reverse-Phase Protein Microarrays and Their Utility in Drug Development -- A Cell Culture System that Mimics Chronic Lymphocytic Leukemia Cells Microenvironment for Drug Screening and Characterization -- 2-Dimensional vs. 3-Dimensional in vitro Tumor Migration and Invasion Assays -- Tumor Spheroid-based Migration Assays for Evaluation of Therapeutic Agents -- The NeuroSphere Assay (NSA) Applied to Neural Stem Cells (NSCs) and Cancer Stem Cells (CSCs).-Genetically Engineered Animal Models for in vivo Target Identification and Validation in Oncology -- Target Validation in Mice by Constitutive and Conditional RNAi -- In vivo Target Validation by Inducible RNAi in Human Xenograft Mouse Models -- Brightfield In Situ Hybridization Methods to Discover Gene Amplifications and Rearrangements in Clinical Samples -- Combined microRNA In Situ Hybridization and Immunohistochemical Detection of Protein Markers.
Keywords: Pharmacology; Medicinal chemistry; Pharmacology/Toxicology.; Medicinal Chemistry